(3JGQjN GdCTQGa GdPjf edchG GdMQejf GdTQjajfs - (3YHO Gddg Hf eMeO YHO GdTchQ GdeTghQs ((3YHOg MSjf GdYHjOi GdTGaYi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje , hHg GdEYGfI hfSCdg GdJhajb jGehLO gPG GdhLhO ef GdYOe (B,(3HYO ajbhd YHO Gddg Hf eMeO YHO GdTchQ GdeTghQ deG QCjJ CMhGd GdReGf cd Mjf JJZjQ s
(3BNQgG (B:s
(3haQL Gddg JYdi bHd hUhdg gPg GdTOI Edi gfG Je Gdfbd ef gPG GdJGQjN GdCZQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN eTQa YHO GdcQje GdNGUI HJYR s
Keywords: (3GdJGQjNs